Influência do Controle Interno na efetividade da Governança Pública nos Municípios Paranaenses - Kinzler, Édina Carine de Souza (2023)
The objective of this study is to verify if the internal control of the municipalities of Paraná is effective in promoting municipal public governance. The study is justified by the relevance of the theme due to the fact that the internal control system and the use of good governance practices in the public sector make it possible to obtain more accurate information regarding the allocation of resources, since it is based on the principles of public administration and law enforcement. The research deals with a descriptive study and has a quantitative approach with the performance of descriptive statistics, correlations and linear regressions. The first specific objective proposed to identify and analyze the structure and operation of the municipalities' internal control regarding aspects of the Control Environment, Risk Assessment, Control Activity, Information and Communication and Monitoring Activity, where it was verified, in the sample of the 102 Municipalities, that the best evaluated internal control component was “Control Environment”, and at the other end (with fewer implemented practices) is the “Monitoring Activity” component. Regarding the maturity of the Municipalities' internal control, it is noted that 41% were classified as improved or advanced (with percentages from 70% to 100%), 51% as intermediate and only 10% as basic or initial. Therefore, most of the internal controls have not reached an improved maturity, needing to expand their practices. Then, the study sought to comparatively analyze the indices that represent the public governance of the municipalities, resulting in the most representative indices, with the highest percentage of practices met, namely, ITP (Public Administration Transparency Index - TCE/PR), IFDM (FIRJAN Municipal Development Index) and RNT (National Transparency Ranking), respectively, and the least representative are IGM (CFA Municipal Governance Index), IEGM (Municipal Management Effectiveness Index) and IFGF (FIRJAN Fiscal Management Index) , respectively. In addition, the municipalities with the highest rates are Maringá, Marechal Cândido Rondon, Matelândia, Palmeiras, Toledo and those with the lowest are Douradina, Esperança Nova, Iracema do Oeste, Santa Lucia and Uniflor. And finally, it was proposed to verify whether the internal control influences the promotion of municipal public governance, where it was verified that there are indications that the internal control exerts a certain influence on the governance of the municipalities in the sample, thus, the activities related to the internal control good municipal management practices (IGM), municipal transparency (RNT) and the effectiveness of municipal public policies (IEGM) exert a certain positive influence